2007
DOI: 10.1097/01.wnp.0000241093.00844.0e
|View full text |Cite
|
Sign up to set email alerts
|

Central Processing of Acute Muscle Pain in Chronic Low Back Pain Patients: An EEG Mapping Study

Abstract: The presence of perceptual sensitization and related brain responses was examined in 14 chronic low back pain (CLBP) patients and 13 healthy controls comparable in age and sex. Multichannel EEG recordings and pain ratings were obtained during the presentation of 800 painful electrical intramuscular and intracutaneous stimuli each to the left m. erector spinae and the left m. extensor digitorum. Perception and pain thresholds were not significantly different between the two groups, though patients showed signif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
77
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 96 publications
(85 citation statements)
references
References 44 publications
(43 reference statements)
6
77
0
2
Order By: Relevance
“…No differences in pain perception threshold and pain tolerance threshold between patients with chronic LBP and HCs were found when the noxious stimulation occurred at the finger, 32 the arm, 38 or other remote sites. 39 One study even observed significant higher pain thresholds in patients with chronic LBP when compared with HCs.…”
Section: Mechanical Pressure And/or Electrical Stimulationmentioning
confidence: 51%
See 1 more Smart Citation
“…No differences in pain perception threshold and pain tolerance threshold between patients with chronic LBP and HCs were found when the noxious stimulation occurred at the finger, 32 the arm, 38 or other remote sites. 39 One study even observed significant higher pain thresholds in patients with chronic LBP when compared with HCs.…”
Section: Mechanical Pressure And/or Electrical Stimulationmentioning
confidence: 51%
“…Evidence for enhanced temporal summation or wind-up comes from studies where pain stimulation is repeated 32,38,41,43 or where continuous stimulation is applied. 42 Mechanical, electrical, or thermal stimulation have been used to induce temporal summation (Table 1, wind-up).…”
Section: Evidence For Enhanced Temporal Summation?mentioning
confidence: 99%
“…The concept of facilitated central gain in chronic LBP is also supported by an EEG mapping study (Diers et al, 2007).…”
Section: Localised and Widespread Hyperalgesiamentioning
confidence: 76%
“…Se ha demostrado que los pacientes con lumbalgia crónica presentan variaciones estructurales y neuroquímicas de la actividad cortical (Diers et al, 2007) en especial la corteza prefrontal dorsolateral, el tálamo y la corteza orbitofrontal (Grachev, Fredrickson y Apkarian, 2000), el tronco cerebral y la corteza somatosensorial (Schmidt-Wilcke et al, 2006). Igualmente, se ha observado la disminución en el flujo de sangre en la sustancia gris periacueductal (Giesecke et al, 2006) redundando en hiperalgesia (Ole Kudsk, Claus Vinther y Kristian, 2009) y contribuye al desarrollo y mantenimiento del estado de dolor crónico (Apkarian, Baliki y Geha, 2009;Tracey y Bushnell, 2009).…”
Section: Discusionunclassified